Polymer composition, method for the preparation thereof and use thereof

By using a specific proportion of inorganic compounds, (meth)acrylic copolymers and polymeric impact modifiers in the thermoplastic polymer, the problem of degradation of performance after adding impact modifiers and processing aids in the prior art is solved, and the effect of improving anti-melt cracking and extrusion productivity is achieved.

CN119875282APending Publication Date: 2025-04-25ARKEMA FRANCE SA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510064161.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-06-07
Filing Date
2017-06-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing thermoplastic polymer compositions are easily lost or reduced in their properties after adding impact modifiers and processing aids, especially when several types or mixtures are added simultaneously.

Method used

By blending these components and dispersing them in the aqueous phase, a material capable of acting as both an impact modifier and a processing aid is prepared by blending these components and dispersing them in the aqueous phase.

Benefits of technology

The anti-melt cracking and extrusion productivity of thermoplastic polymers is improved while maintaining the properties of the material and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005243745510000201
    Figure BDA0005243745510000201
  • Figure BDA0005243745510000202
    Figure BDA0005243745510000202
  • Figure BDA0005243745510000203
    Figure BDA0005243745510000203
Patent Text Reader

Abstract

The invention relates to a polymer composition comprising an impact modifier, a processing aid and a mineral filler and to a method for the production thereof and to the use thereof. In particular, the invention relates to polymer compositions comprising impact modifiers, processing aids and mineral fillers, and to the use thereof for thermoplastic polymers. The invention more particularly relates to a process for the preparation of polymer compositions comprising impact modifiers, processing aids and mineral fillers and to the use thereof for the transformation and / or processing of thermoplastic polymers.
Need to check novelty before this filing date? Find Prior Art

Description

This application is a divisional application of application number 201780048416.2, and the application date of application number 201780048416.2 is June 7, 2017. [Field of the Invention] The present invention relates to a polymer composition comprising an impact modifier, a processing aid and a mineral filler, a method for preparing the same and the use thereof.

[0002] The invention relates in particular to polymer compositions comprising an impact modifier, a processing aid and a mineral filler and to their use for thermoplastic polymers.

[0003] The invention more particularly relates to a process for the preparation of a polymer composition comprising an impact modifier, a processing aid and a mineral filler and to its use for the transformation and / or processing of thermoplastic polymers.

[0004] [Technical issues] Many types of additives and fillers are used in thermoplastic polymer compositions in general, and halogenated polymer compositions in particular, for a variety of reasons. They can bulk up the composition, increase stiffness and strength, and shorten cycle time. They prevent hang-up in the die and neutralize degradation products. Fillers can also be used to increase color, opacity, and conductivity or they can be used as low-cost materials to reduce the cost of the composition because fillers are cheaper than other ingredients in the formulation.

[0005] However, the addition of additives and fillers to thermoplastic polymers can also adversely alter the properties of the thermoplastic polymer composition, ie, certain properties or performances are lost or significantly reduced, especially when several are added simultaneously or in mixtures thereof.

[0006] Polymer compositions comprising polymers having specific properties (such as polymer composition, glass transition temperature or specific molecular weight range, just to mention some properties) are used as additives to thermoplastic polymer compositions in general and halogenated polymer compositions in particular to enhance the processing properties of these various polymer compositions or plastic resins or to improve their conversion and / or processing properties. These additives are therefore also called processing aids.

[0007] Small amounts of processing aids in thermoplastic polymer compositions in general, and halogenated polymer compositions in particular, can improve processing characteristics by accelerating the melting process of the thermoplastic polymer compositions in general, and halogenated polymer compositions in particular.

[0008] Other polymer compositions comprising polymers having specific properties (such as polymer composition, glass transition temperature or structure, to mention some properties) are also used as additives to thermoplastic polymer compositions in general, and halogenated polymer compositions in particular, to improve the impact resistance of the compositions or objects made from these various polymers or plastic resins. These additives are therefore also called impact modifiers.

[0009] The additive polymer composition is compatible with thermoplastic polymer compositions in general, and halogenated polymer compositions in particular.

[0010] The object of the present invention is to propose polymer compositions which can be added as additives to thermoplastic polymers.

[0011] The present invention also aims to propose a polymer composition which acts simultaneously as an impact modifier and a processing aid.

[0012] It is also an object of the present invention to provide a polymer composition that can be used to improve the melt fracture resistance of a thermoplastic polymer.

[0013] Another object of the present invention is to provide a polymer composition that can be used to increase the extrusion productivity of thermoplastic polymers.

[0014] Another object of the present invention is to reduce the price of a polymer composition that acts as both a processing aid and an impact modifier for a thermoplastic polymer composition by adding low cost components without negatively affecting the properties of the thermoplastic polymer composition.

[0015] Yet another object of the present invention is a method of making a polymer composition that acts simultaneously as an impact modifier and a processing aid and increases the extrusion productivity of thermoplastic polymers.

[0016] Another object is to provide a method for preparing a polymer composition that can be used to increase the conversion productivity of the polymer composition and to increase the impact strength.

[0017] [Background of the invention] Prior art Document US2009 / 0111915 discloses acrylic copolymers for highly filled compositions. The document discloses in particular filled polyvinyl chloride (PVC) materials - as flooring compositions comprising 70 to 95% by weight of filler, 1 to 15% by weight of PVC and 0.5 to 4% by weight of acrylic copolymers or siding or pipe compositions comprising 15 to 35% by weight of filler, 50 to 95% by weight of PVC and 0.25 to 6% by weight of acrylic copolymers.

[0018] Document WO 2010 / 099160 discloses a composite polymer modifier. The document discloses a composite polymer modifier consisting of 99 wt % to 1 wt % of an inorganic filler, 1 wt % to 99 wt % of a polymeric processing aid, and 0 wt % to 80 wt % of an impact modifier. The impact modifier is optional, but is used in some embodiments. The document does not disclose specific advantages of certain impact modifier compositions.

[0019] Document US 3,373,229 discloses a vinyl polymer composition. The composition comprises polyvinyl chloride and a high molecular weight methyl methacrylate polymer or a copolymer of methyl methacrylate and a small amount of alkyl acrylate as a processing aid. The composition may contain a filler.

[0020] None of the prior art documents discloses such specific polymer compositions comprising an inorganic compound, a (meth)acrylic copolymer and a polymeric impact modifier, nor a method for its preparation or its use. [Summary of the Invention] Surprisingly, it has been found that a polymer composition P1 improves the melt fracture resistance of thermoplastic polymers while providing good impact properties. a) 30 to 60% by weight of an inorganic compound (F), b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) and c) polymeric impact modifier (IM1); It is characterized in that the three components a), b) and c) add up to 100% by weight.

[0022] It has also been surprisingly found that a method for preparing a polymer composition P1 comprising a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) polymeric impact modifier (IM1); It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: The three components a), b) and c) are blended, with both components b) and c) and at least 83.33% by weight of compound a) being in the form of a dispersion in the aqueous phase during the blending step.

[0023] It has also been surprisingly found that a method for preparing a polymer composition P1 comprising a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) polymeric impact modifier (IM1); It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: i) blending the three components a), b) and c), wherein the two components b) and c) and at least 83.33% by weight of compound a) are in the form of a dispersion in the aqueous phase during the blending step, ii) drying the blend obtained in step i).

[0024] It has also been surprisingly found that a polymer composition P1 can be used to increase the extrusion productivity of thermoplastic polymers, comprising a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) polymeric impact modifier (IM1); It is characterized in that the three components a), b) and c) add up to 100% by weight. [Detailed description of the invention] According to a first aspect, the present invention relates to a polymer composition P1 comprising a) 30 to 60% by weight of an inorganic compound (F), b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) and c) polymeric impact modifier (IM1); It is characterized in that the three components a), b) and c) add up to 100% by weight.

[0026] According to a second aspect, the present invention relates to a polymer composition P1 comprising a) 30 to 60% by weight of an inorganic compound (F), The inorganic compound (F) consists of a mineral filler (F1) and a flow aid (F2), wherein the weight ratio (F1) / (F2) is at least 5 / 1, b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) and c) polymeric impact modifier (IM1); It is characterized in that the three components a), b) and c) add up to 100% by weight.

[0027] In a third aspect, the present invention relates to a method for preparing a polymer composition P1, wherein the polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) Polymeric impact modifier (IM1) It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: The three components a), b) and c) are blended, while both components b) and c) and at least 83.33% by weight of compound a) are in the form of a dispersion in the aqueous phase during the blending step.

[0028] In a fourth aspect, the present invention relates to a method for preparing a polymer composition P1, wherein the polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) The inorganic compound (F) consists of a mineral filler (F1) and a flow aid (F2), wherein the weight ratio (F1) / (F2) is at least 5 / 1, b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) and c) polymeric impact modifier (IM1); It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: The three components a), b) and c) are blended, while the three components b), c) and the mineral filler (F1) are in the form of a dispersion in the aqueous phase during the blending step.

[0029] In a fifth aspect, the present invention relates to a method for preparing a polymer composition P1, wherein the polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) Polymeric impact modifier (IM1) It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: i) blending the three components a), b) and c), wherein the two components b) and c) and at least 83.33% by weight of compound a) are in the form of a dispersion in the aqueous phase during the blending step, ii) drying the blend obtained in step i).

[0030] In a sixth aspect, the present invention relates to a method for preparing a polymer composition P1, wherein the polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) The inorganic compound (F) consists of a mineral filler (F1) and a flow aid (F2), wherein the weight ratio (F1) / (F2) is at least 5 / 1, b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) and c) polymeric impact modifier (IM1); It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: i) blending the three components a), b) and c), with the three components b), c) and the mineral filler (F1) being in the form of a dispersion in the aqueous phase during the blending step ii) drying the blend obtained in step i).

[0031] In a seventh aspect, the present invention relates to a method for preparing a polymer composition P2 comprising a polymer composition P1, wherein the polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) a polymeric impact modifier (IM1), characterized in that the three components a), b) and c) add up to 100% by weight, and the polymer composition P2 further comprises d) Thermoplastic polymer TP1 The method comprises the following steps: The composition P1 and the thermoplastic polymer TP1 are blended.

[0032] In an eighth aspect, the present invention relates to the use of a polymer composition P1 for improving the melt fracture resistance of a thermoplastic polymer TP1, wherein the polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) a polymeric impact modifier (IM1), It is characterized in that the three components a), b) and c) add up to 100% by weight.

[0033] In a ninth aspect, the present invention relates to the use of a polymer composition P1 for converting a polymer composition P2 comprising said polymer composition P1 and a thermoplastic polymer TP1, said polymer composition P1 comprising a) 30 to 60 wt% of an inorganic compound (F) b) 5 to 15 wt% of a (meth)acrylic copolymer (A1) c) a polymeric impact modifier (IM1), It is characterized in that the three components a), b) and c) add up to 100% by weight.

[0034] The term "polymer composition" is used to mean that the composition consists of at least 40% by weight of a polymer.

[0035] The term "copolymer" is used to mean that the polymer is composed of at least two different monomers.

[0036] The term "(meth)acrylic" is used to refer to all types of acrylic and methacrylic monomers.

[0037] The term "(meth)acrylic polymer" used means that the (meth)acrylic polymer mainly comprises a polymer containing 50% by weight or more of a (meth)acrylic monomer constituting the (meth)acrylic polymer.

[0038] The term "polymer powder" is used to refer to a polymer comprising powder particles in the range of at least 1 micrometer (μm) obtained by agglomeration of a primary polymer comprising nanoscale particles.

[0039] The term "primary particles" used refers to spherical polymers comprising nanoscale particles. The primary particles preferably have a weight average particle size between 20 nanometers and 500 nanometers.

[0040] As used herein, "multistage polymer" refers to polymers formed sequentially by a multistage polymerization process. Preferred is a multistage emulsion polymerization process, wherein the first polymer is a first stage polymer and the second polymer is a second stage polymer, ie the second polymer is formed by emulsion polymerization in the presence of the first emulsion polymer.

[0041] The term "dispersion" is used to refer to a colloidal system having a continuous liquid phase and a discontinuous solid phase distributed throughout the continuous phase.

[0042] The term "emulsion" is used to refer to a liquid / liquid mixture of a liquid discontinuous phase in a liquid continuous phase.

[0043] The term "PVC" is understood to mean polyvinyl chloride in the form of a homopolymer or a copolymer comprising at least 50% by weight of vinyl chloride.

[0044] The term "filler" is used to understand solid extenders added to polymers to enhance properties and / or reduce costs.

[0045] The term "glidant" is understood to be an anti-caking agent which achieves good flowability of the powder and avoids agglomeration.

[0046] The abbreviation "phr" means parts per hundred parts of resin. For example, 15 phr of filler in a PVC formulation means that 15 kg of filler is added to 100 kg of PVC.

[0047] The phrase "the sum of the three components a), b) and c) is 100% by weight" means that the ratio of the three components a), b) and c) is calculated only by the sum of these three components. If there are other additional components besides a), b) and c), they are not included in the calculation of the weight ratio between the three.

[0048] Reference to a range of x to y in the present invention is intended to include the upper and lower limits of this range, corresponding to at least x and at most y.

[0049] In the present invention, when a range is mentioned between x and y, it is intended to exclude the upper and lower limits of this range, which is equivalent to greater than x and less than y.

[0050] Regarding the polymer composition P1 of the present invention, it comprises at least three components: a) 30% to 60% by weight of an inorganic compound (F), b) 2% to 15% by weight of a (meth)acrylic copolymer (A1) and c) a polymeric impact modifier (IM1), wherein the relative amounts of these three components are selected such that the sum of these three components is 100% by weight. The component c) polymeric impact modifier (IM1) in the polymer composition P1 is between 25% and 68% by weight.

[0051] Component b) can also be a mixture of several (meth)acrylic copolymers (A1) to (Ax). The individual (meth)acrylic copolymers have specific different properties.

[0052] Component c) can also be a mixture of several polymeric impact modifiers (IM1) to (IMx). The individual polymeric impact modifiers have specific different properties.

[0053] The polymer composition P1 preferably comprises: a) between 30% and 60% by weight of an inorganic compound (F), b) between 2% and 15% by weight of a (meth)acrylic copolymer (A1) and c) a polymeric impact modifier (IM1), the relative amounts c) being selected so that the three components add up to 100% by weight.

[0054] The inorganic compound (F) consists of a mineral filler (F1) and a flow aid (F2), wherein the weight ratio (F1) / (F2) is at least 5 / 1.

[0055] More preferably, the composition P1 of the invention comprises: a) between 30% and 60% by weight of an inorganic compound (F), b) between 2% and 12% by weight of a (meth)acrylic copolymer (A1) and c) a polymeric impact modifier (IM1), such that the three components add up to 100% by weight in relative amounts selected c). Even more preferably, the composition P1 comprises: a) between 30% and 50% by weight of an inorganic compound (F), b) between 3% and 10% by weight of a (meth)acrylic copolymer (A1) and c) a polymeric impact modifier (IM1), such that the three components add up to 100% by weight in relative amounts selected c).

[0056] Advantageously, the composition P1 of the invention comprises: a) between 40% and 50% by weight of an inorganic compound (F), b) between 4% and 10% by weight of a (meth)acrylic copolymer (A1) and c) a polymeric impact modifier (IM1), the relative amounts c) being chosen so that these three components add up to 100% by weight.

[0057] The polymer composition P1 according to the invention is preferably in the form of a powder comprising these three components. The powder consists of particles of aggregated particles of these three components. These particles are primary particles.

[0058] As regards the polymer powder of the invention, it has a volume median particle size D50 between 1 μm and 500 μm. The volume median particle size of the polymer powder is preferably between 10 μm and 450 μm, more preferably between 15 μm and 400 μm, advantageously between 20 μm and 300 μm.

[0059] The D10 of the volume particle size distribution is at least 7 μm, preferably 10 μm.

[0060] The D90 of the volume particle size distribution is at most 800 μm, preferably at most 500 μm.

[0061] The powder according to the invention is homogeneous with respect to the composition concerning these three components.

[0062] Homogeneous in the present invention means that there is no significant change in the entire composition. If one or several small samples (1 gram or less, containing several powder particles) are taken out from a larger amount (1 kilogram) of the composition, the composition of the weight ratio of the three components in the small sample does not change significantly compared with other small samples and the total composition. No significant change means that the change is less than 30% relative to the total composition. As an example, if the total composition P1 contains 40 wt% of an inorganic compound (F), 10 wt% of a (meth)acrylic copolymer (A1) and 50 wt% of a polymeric impact modifier (IM1), a first small sample taken from the total composition containing 35 wt% of an inorganic compound (F), 11 wt% of a (meth)acrylic copolymer (A1) and 54 wt% of a polymeric impact modifier (IM1) or a second small sample taken from the total composition containing 42 wt% of an inorganic compound (F), 10 wt% of a (meth)acrylic copolymer (A1) and 48 wt% of a polymeric impact modifier (IM1) means a uniform composition because the variation in the ratio of each component in the small sample is within a 30% variation relative to the total composition of the sample.

[0063] The compositional variation within the composition is preferably less than 25%, more preferably less than 20%.

[0064] Ideally, each powder particle or granule comprises all three components a), b) and c) and consists of aggregated particles of these three components.

[0065] The polymer composition P1 according to the invention which is preferably in powder form is more preferably a dry powder. Dry means that the powder has a certain maximum moisture level.

[0066] The dry polymer composition P1 according to the invention in powder form comprises less than 3 wt. % moisture, preferably less than 1.5 wt. % moisture, more preferably less than 1.2 wt. % moisture.

[0067] The dry polymer composition P1 in powder form according to the invention may additionally contain a flow aid (F2). The flow aid (F2) is preferably an inorganic compound. The flow aid (F2) is therefore part of the inorganic compound (F) of the composition P1. The inorganic compound (F) consists of the flow aid (F2) and the inorganic filler (F1): (F) = (F1) + (F2). The amount of the flow aid (F2) in the polymer composition P1 is much smaller than that of the inorganic filler (F1). The amount of (F1) is at least 5 times the amount of (F2).

[0068] The density of the polymer composition P1 is at least 1.25 g / cm3, preferably at least 1.3 g / cm3, more preferably at least 1.33 g / cm3.

[0069] The density of the polymer composition P1 is at most 1.75 g / cm3, preferably at most 1.7 g / cm3, more preferably at most 1.67 g / cm3.

[0070] Advantageously, the polymer composition P1 has a density between 1.25 g / cm3 and 1.75 g / cm3, more advantageously between 1.3 g / cm3 and 1.7 g / cm3.

[0071] As regards the inorganic compound (F), it is an inorganic filler or a mineral filler (F1), or it comprises an inorganic filler or a mineral filler (F1) and a flow aid (F2).

[0072] The inorganic compound (F) preferably comprises a mineral filler (F1) and a flow aid (F2). More preferably, the weight ratio (F1) / (F2) is at least 5 / 1.

[0073] As mineral fillers (F1), mention may be made of glass fibers, hollow glass microspheres, inorganic compounds such as minerals and salts including calcium carbonate (CaCO3), silicon dioxide, silicates such as calcium silicate or calcium metasilicate, clays such as bentonite, mica, talc, aluminum trihydrate, magnesium hydroxide, metal oxides or a combination of two or more thereof.

[0074] The mineral filler (F1) is preferably chosen from calcium carbonate, titanium dioxide or calcined clay, silica (fumed or precipitated silica), clay, montmorillonite (nanoclay), zeolite, perlite or any other type of inorganic material available as a slurry.

[0075] The mineral filler (F1) is more preferably selected from calcium carbonate, calcined clay, silica (fumed or precipitated silica), clay, montmorillonite (nanoclay), zeolite or perlite.

[0076] The mineral filler (F1) of the inorganic compound (F) may also be a mixture of several mineral fillers (F1a) to (F1x).

[0077] In a more preferred embodiment, the mineral filler (F1) is calcium carbonate (CaCO3).

[0078] Advantageously, the calcium carbonate is selected from precipitated calcium carbonate (PCC), ground natural calcium carbonate (GCC) or nanosized particles of precipitated calcium carbonate (NPCC).

[0079] The mineral filler (F1) or at least a portion of the mineral filler (F1) can also be used in the process for preparing the polymer composition P1 in the form of a slurry.

[0080] The filler (F1) or at least a portion of the mineral filler (F1) blended with the (meth)acrylic copolymer (A1) and the polymeric impact modifier (IM1) is preferably in the form of a slurry.

[0081] As regards the slurry of the mineral filler, it is an aqueous dispersion of the mineral filler having a solids content preferably between 5% and 90% by weight, advantageously between 50% and 80% by weight. This aqueous dispersion may contain optional specific surfactants, dispersants, additives or filler surface treatment agents which may advantageously improve the slurry qualities (stability, viscosity or compatibility with the host polymer matrix).

[0082] As for the flow aid (F2), it is an inorganic powder.

[0083] The glidant (F2) may also be a mixture of several glidants (F2a) to (F2x).

[0084] Advantageously, the glidant (F2) is chosen from calcium carbonate (CaCO3).

[0085] As for the (meth)acrylic copolymer (A1), it is a (meth)acrylic copolymer containing at least 50% by weight of polymerized units derived from methyl methacrylate.

[0086] The (meth)acrylic copolymer (A1) preferably has a glass transition temperature of less than 106°C.

[0087] More preferably, polymer (A1 ) comprises one or more comonomers copolymerizable with methyl methacrylate, as long as polymer (A1 ) has a glass transition temperature of less than 106°C.

[0088] The comonomer(s) in copolymer (A1) are preferably selected from (meth)acrylic monomers and / or vinyl monomers.

[0089] The (meth)acrylic comonomer in the (meth)acrylic copolymer (A1) includes monomers selected from C1 to C12 alkyl (meth)acrylates. The (meth)acrylic comonomer in the polymer (A1) more preferably includes C1 to C4 alkyl methacrylate monomers and / or C1 to C8 alkyl acrylate monomers.

[0090] The acrylic or methacrylic comonomer of the (meth)acrylic copolymer (A1) or the two (meth)acrylic copolymers (A1a) and (A1b) is most preferably selected from methyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate and mixtures thereof, as long as the (meth)acrylic copolymer (A1) or the mixture of the two (meth)acrylic copolymers (A1a) and (A1b) has a glass transition temperature of less than 106°C.

[0091] The (meth)acrylic copolymer (A1) preferably comprises at most 90% by weight, more preferably at most 85% by weight, advantageously at most 81% by weight of polymerized units derived from methyl methacrylate.

[0092] In a specific embodiment, the (meth)acrylic copolymer (A1) is a copolymer of methyl methacrylate and ethyl acrylate and / or butyl acrylate.

[0093] The glass transition temperature Tg of the (meth)acrylic polymer (A1) comprising at least 50 wt% of polymerized units derived from methyl methacrylate is more preferably between 60°C and 106°C, still more preferably between 65°C and 100°C, advantageously between 70°C and 100°C.

[0094] The glass transition temperature Tg can be estimated, for example, by dynamic methods such as thermomechanical analysis.

[0095] Preferably, the (meth)acrylic copolymer (A1) or the two (meth)acrylic copolymers (A1a) and (A1b) comprising at least 50 wt. % of polymerized units derived from methyl methacrylate have a weight average molecular weight Mw of at least 1 000 000 g / mol, preferably at least 1 500 000 g / mol, more preferably at least 2 000 000 g / mol, advantageously at least 2 500 000 g / mol, most advantageously at least 3 000 000 g / mol.

[0096] Preferably, the (meth)acrylic copolymer (A1) or the two (meth)acrylic copolymers (A1a) and (A1b) comprising at least 50 wt. % of polymerized units derived from methyl methacrylate has a weight average molecular weight Mw of less than 10,000,000 g / mol, preferably less than 9,000,000 g / mol, more preferably less than 8,000,000 g / mol, advantageously less than 8,500,000 g / mol, most advantageously 7,000,000 g / mol.

[0097] The (meth)acrylic copolymer (A1) comprising at least 50% by weight of polymerized units derived from methyl methacrylate is preferably prepared by emulsion polymerization to produce an aqueous dispersion of spherical polymer particles of the (meth)acrylic copolymer (A1).

[0098] One possible variant of the process for preparing the aqueous dispersion of spherical polymer particles comprising the (meth)acrylic copolymer (A1) is by using a multistage process.

[0099] In the process of one stage of the multi-stage method, a (meth)acrylic copolymer (A1) is prepared.

[0100] The spherical polymer particles comprising the (meth)acrylic copolymer (A1) have a weight average particle size between 20 nm and 500 nm. The weight average particle size of the polymer is preferably between 50 nm and 400 nm, more preferably between 75 nm and 350 nm, advantageously between 80 nm and 300 nm.

[0101] As regards the polymeric impact modifier (IM1), it is preferably polymer particles having a multilayer structure.

[0102] The polymer particles with multilayer structure are more or less spherical. The polymer particles have a weight average particle size (diameter) between 20nm and 500nm. The weight average particle size of the polymer particles is preferably between 50nm and 400nm, more preferably between 75nm and 350nm, advantageously between 80nm and 300nm.

[0103] The polymer particles according to the present invention are obtained by a multi-stage process, such as two-stage or three-stage or more, each stage producing a layer, the whole process producing particles having a multi-layer structure.

[0104] The polymeric impact modifier (IM1) is in the form of polymer particles having a multilayer structure comprising at least one layer (IM1L1) comprising a polymer (L1) having a glass transition temperature below 0°C and at least another layer (IM1L2) comprising a polymer (L2) having a glass transition temperature above 45°C.

[0105] More preferably, the glass transition temperature Tg of polymer (L1) is between -100°C and 0°C, even more preferably between -80°C and 0°C, advantageously between -80°C and -20°C, more advantageously between -70°C and -20°C.

[0106] The glass transition temperature Tg of polymer (L2) is preferably between 60 and 150° C. The glass transition temperature Tg of polymer (L2) is more preferably between 80 and 140° C., advantageously between 90 and 135° C., more advantageously between 90 and 130° C.

[0107] To obtain samples of the respective polymers (L1) and (L2), they may be prepared individually rather than by a multi-stage process, so that the glass transition temperature Tg of each polymer of each stage can be evaluated and measured more easily individually.

[0108] The weight ratio of layer (IM1L1) / layer (IM1L2) in the multistage polymer is preferably at least 70 / 30, more preferably at least 80 / 20, even more preferably at least 85 / 15, advantageously at least 86 / 14, more advantageously 87 / 13, even more advantageously 88 / 12, most advantageously 89 / 11.

[0109] The weight ratio of layer (IM1L1) / layer (IM1L2) in the multistage polymer is preferably in the weight range of 70 / 30 to 99 / 1, more preferably 80 / 20 to 98 / 2, even more preferably 85 / 15 to 97 / 3, advantageously 86 / 14 to 97 / 3, more advantageously 87 / 13 to 97 / 3, even more advantageously 88 / 12 to 97 / 3, most advantageously 89 / 11 to 96 / 4.

[0110] The polymer L1 preferably constitutes more than 85% by weight, more preferably more than 86% by weight, advantageously more than 87% by weight of the polymeric impact modifier (IM1).

[0111] The multilayer structure of IM1 may have different structures. The layer (IM1L1) comprising a polymer (L1) having a glass transition temperature below 0°C may be the core or an intermediate layer of the polymeric impact modifier (IM1), but never the outermost layer. The layer (IM1L2) comprising a polymer (L2) having a glass transition temperature above 45°C may be the outermost layer.

[0112] The layer (IM1L2) comprising polymer (L2) is preferably a (meth)acrylic copolymer comprising at least 50% by weight of polymerized units derived from methyl methacrylate. Preferably, the polymer (L2) or a majority of the polymer (L2) of the layer (IM1L2) is grafted onto an underlying layer.

[0113] In a first preferred embodiment of (IM1), the polymer (L1) having a glass transition temperature below 0° C. is a (meth)acrylic polymer comprising at least 50% by weight of monomers from the group of alkyl acrylates.

[0114] More preferably, polymer (L1) comprises one or more comonomers copolymerizable with the alkyl acrylate, as long as polymer (A1) has a glass transition temperature of less than 0°C.

[0115] The comonomer(s) in polymer (L1) are preferably selected from (meth)acrylic monomers and / or vinyl monomers.

[0116] The (meth)acrylic comonomer in polymer (L1) comprises a monomer selected from C1 to C12 alkyl (meth)acrylates. The (meth)acrylic comonomer in polymer (L1) further preferably comprises C1 to C4 alkyl methacrylates and / or C1 to C8 alkyl acrylates.

[0117] The acrylic or methacrylic comonomer of polymer (L1) is most preferably selected from methyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate and mixtures thereof, as long as polymer (L1) has a glass transition temperature of less than 0°C.

[0118] The polymer (L1) is preferably crosslinked. This means that a crosslinking agent is added to another monomer or to other monomers. The crosslinking agent contains at least two polymerizable groups.

[0119] In a specific embodiment, polymer (L1) is a homopolymer of butyl acrylate.

[0120] In another specific embodiment, polymer (L1) is a copolymer of butyl acrylate and at least one crosslinking agent. The crosslinking agent constitutes less than 5% by weight of this copolymer.

[0121] The glass transition temperature Tg of the polymer (L1) of the first embodiment is more preferably between -100°C and 0°C, still more preferably between -100°C and -5°C, advantageously between -90°C and -15°C, more advantageously between -90°C and -25°C.

[0122] In a second preferred embodiment, the polymer (L1) having a glass transition temperature below 0° C. comprises at least 50% by weight of polymerized units derived from isoprene or butadiene and the stage or layer (IML1) is the innermost layer of a polymer particle having a multilayer structure. In other words, the stage used to make the layer (IM1L1) comprising polymer (L1) is the core of the polymer particle.

[0123] For example, as polymer (L1) of the core of the second embodiment, mention may be made of isoprene homopolymers or butadiene homopolymers, isoprene-butadiene copolymers, copolymers of isoprene with up to 98% by weight of vinyl monomers and copolymers of butadiene with up to 98% by weight of vinyl monomers. The vinyl monomer may be styrene, alkylstyrene, acrylonitrile, alkyl (meth)acrylates or butadiene or isoprene. In one embodiment, the core is a butadiene homopolymer.

[0124] More preferably, the glass transition temperature Tg of the polymer (L1) of the second embodiment comprising at least 50 wt.-% of polymerized units derived from isoprene or butadiene is between -100°C and 0°C, even more preferably between -100°C and -5°C, advantageously between -90°C and -15°C, even more advantageously between -90°C and -25°C.

[0125] As regards the thermoplastic polymer TP1, it is selected from halogen-containing polymers such as polyvinyl chloride, polyamide, polymethyl methacrylate, polystyrene, polycarbonate, polyesters such as polyethylene terephthalate, polybutylene terephthalate, polycyclohexanedimethanol terephthalate, and polyolefins.

[0126] In a first preferred embodiment, the thermoplastic polymer TP1 is a halogen-containing polymer.

[0127] As regards halogen-containing polymers, mention may be made of: Homopolymers and copolymers of vinyl chloride (PVC) and homopolymers and copolymers of vinylidene chloride (PVDC), vinyl resins containing vinyl chloride units in their structure, such as copolymers of vinyl chloride and vinyl esters of aliphatic acids, especially vinyl acetate, copolymers of vinyl chloride with acrylates and methacrylates and with acrylonitrile, copolymers of vinyl chloride with diene compounds and unsaturated dicarboxylic acids or their anhydrides, such as copolymers of vinyl chloride with diethyl maleate, diethyl fumarate or maleic anhydride, post-chlorinated polymers and copolymers of vinyl chloride, copolymers of vinyl chloride and vinylidene chloride with unsaturated aldehydes, ketones, etc., such as acrolein, crotonaldehyde, vinyl methyl ketone, vinyl methyl ether, vinyl isobutyl ether, etc.; polymers of vinylidene chloride and copolymers thereof with vinyl chloride and other polymerizable compounds; Polymers of vinyl chloroacetate and dichlorodivinyl ether; chlorinated polymers of vinyl carboxylates, such as vinyl acetate, vinyl propionate, vinyl butyrate, chlorinated polymers of acrylic acid and α-substituted acrylic acid, such as methacrylic acid, nitriles, amides, alkyl esters such as acrylonitrile, (meth)acrylamide, methyl (meth)acrylate, butyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate; Vinyl aromatic derivatives, e.g. polymers of styrene and dichlorostyrene; chlorinated rubber; Chlorinated polymers of olefins, for example ethylene, propylene, 1-butene, (2.2.1)bicycloheptene-2, (2.2.1)bicycloheptene-2,5-diene; polymers and post-chlorinated polymers of chloroprene and their copolymers with vinyl chloride, chlorinated natural and synthetic rubbers, and mixtures of these polymers with each other or with other polymerizable compounds.

[0128] Grafted halogen-containing copolymers, wherein the halogen-containing polymer moiety is grafted onto a (meth)acrylic homopolymer or copolymer in particle form, which may or may not be crosslinked.

[0129] The halogen-containing polymer is preferably a thermoplastic polymer rather than an elastomeric polymer. The thermoplastic polymer has a glass transition temperature of at least 40°C, preferably 50°C.

[0130] The halogen in the halogen-containing polymer is preferably selected from fluorine or chlorine, the halogen being advantageously chlorine.

[0131] The chlorine-containing polymer is selected from the following polymers or polymer mixtures: homopolymers of vinyl chloride, such as polyvinyl chloride, polyvinylidene chloride, chlorinated polyvinyl chloride, post-chlorinated polyvinyl chloride and copolymers formed by polymerization of vinyl chloride monomer and up to 40% of comonomers such as vinyl acetate, vinyl butyrate, vinylidene chloride, propylene, methyl methacrylate, etc., and chlorine-containing polymers containing other polymers, such as chlorinated polyethylene, acrylonitrile, butadiene, styrene terpolymers, methyl methacrylate, butadiene, styrene terpolymers; polyacrylate resins, polymethyl methacrylate resins and terpolymers of alkyl acrylates, methyl methacrylate, butadiene. The chlorine-containing polymer is preferably polyvinyl chloride or post-chlorinated polyvinyl chloride.

[0132] The chlorine-containing polymer is preferably chosen from homopolymers and copolymers of vinyl chloride (VC); comprising at least 50% by weight of VC units, preferably at least 70% by weight of VC units, more preferably at least 80% by weight of VC units, advantageously at least 85% by weight of VC units; or mixtures thereof.

[0133] As regards the process for preparing the polymer composition P1 according to the invention, the polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) Polymeric impact modifier (IM1) It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: The three components a), b) and c) are blended, while both components b) and c) and at least 83.33% by weight of compound a) are in the form of a dispersion in the aqueous phase during the blending step.

[0134] As regards a first preferred method for preparing a polymer composition P1 according to the invention, said polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) Polymeric impact modifier (IM1) It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: i) blending the three components a), b) and c), wherein the two components b) and c) and at least 83.33% by weight of compound a) are in the form of a dispersion in the aqueous phase during the blending step ii) drying the blend obtained in step i).

[0135] As regards a second preferred method for preparing a polymer composition P1 according to the invention, said polymer composition P1 comprises a) 30 to 60% by weight of an inorganic compound (F), The inorganic compound (F) consists of a mineral filler (F1) and a flow aid (F2), wherein the weight ratio (F1) / (F2) is at least 5 / 1, b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) Polymeric impact modifier (IM1) It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: The three components a), b) and c) are blended, while the three components b), c) and (F1) are in the form of dispersion in the aqueous phase during the blending step.

[0136] More preferably, the method for preparing a polymer composition P1, said polymer composition P1 comprising a) 30 to 60 wt% of an inorganic compound (F) The inorganic compound (F) consists of a mineral filler (F1) and a flow aid (F2), wherein the weight ratio (F1) / (F2) is at least 5 / 1, b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) Polymeric impact modifier (IM1) It is characterized in that the three components a), b) and c) add up to 100% by weight, and the method comprises the following steps: i) blending the three components a), b) and c), while the three components b), c) and (F1) are in the form of a dispersion in the aqueous phase during the blending step, ii) drying the blend obtained in step i).

[0137] Alternatively the process may further comprise the step of recovering the resulting blend of the previous step to form or as polymer powder.

[0138] The amounts of the aqueous dispersions of the three components a), b) and c) or (F1) are selected based on the solids content of the respective dispersions in order to obtain the composition of the polymer composition P1 based on the solids fraction.

[0139] The recovery step of the process for manufacturing the polymer composition according to the invention is preferably carried out by coagulation or by spray drying. Obviously, spray drying combines recovery and drying in one process step.

[0140] In the case of spray drying, the individual dispersions of components a), b) and c) may be blended or mixed and the liquid mixture then added to the spray drying apparatus. The dispersions may also be blended or mixed within the spray drying apparatus during the recovery step.

[0141] Spray drying is the preferred recovery and / or drying method of the process for preparing polymer composition P1.

[0142] The dried polymer composition P1 contains less than 3 wt. % water, preferably less than 1.5 wt. % water, more preferably less than 1.2 wt. % water.

[0143] The present invention also relates to a method for preparing a polymer composition P2 comprising a polymer composition P1, wherein the polymer composition P1 comprises a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) a polymeric impact modifier (IM1), characterized in that the three components a), b) and c) add up to 100% by weight, and the polymer composition P2 further comprises d) Thermoplastic polymer TP1 The method comprises the following steps: The composition P1 and the thermoplastic polymer TP1 are blended.

[0144] Preferably, in the process for preparing polymer composition P2, polymer composition P1 is prepared according to the process described above.

[0145] The inorganic compound (F), the (meth)acrylic copolymer (A1), the polymeric impact modifier (IM1), the polymer composition P1 and the thermoplastic polymer TP1 are the same as defined above.

[0146] Composition P1 and thermoplastic polymer TP1 are preferably blended by means known to those skilled in the art for blending polymer compositions, such as dry blending or compounding of the components followed by melt processing.

[0147] The ratio of polymer composition P1 in polymer composition P2 is between 1 and 20 phr, preferably between 2 and 15 phr, more preferably between 3 and 12 phr and advantageously between 3 and 10 phr.

[0148] The present invention relates to the use of a polymer composition P1 for improving the melt fracture resistance of a thermoplastic polymer TP1, said polymer composition P1 comprising a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) a polymeric impact modifier (IM1), It is characterized in that the three components a), b) and c) add up to 100% by weight.

[0149] After this use, the thermoplastic polymer TP1 comprises the polymer composition P1 and gives rise to the polymer composition P2.

[0150] Preferably, in the process for preparing polymer composition P2, polymer composition P1 is prepared according to the process described above.

[0151] The inorganic compound (F), the (meth)acrylic copolymer (A1), the polymeric impact modifier (IM1), the polymer composition P1 and the thermoplastic polymer TP1 are the same as defined above.

[0152] The present invention relates to the use of a polymer composition P1 for converting a polymer composition P2 comprising said polymer composition P1 and a thermoplastic polymer TP1, said polymer composition P1 comprising a) 30 to 60 wt% of an inorganic compound (F) b) 2 to 15 wt% of a (meth)acrylic copolymer (A1) c) a polymeric impact modifier (IM1), It is characterized in that the three components a), b) and c) add up to 100% by weight.

[0153] Preferably, in the process for preparing polymer composition P2, polymer composition P1 is prepared according to the process described above.

[0154] The inorganic mineral filler (F), the (meth)acrylic copolymer (A1 ), the polymeric impact modifier (IM1 ), the polymer composition P1 and the thermoplastic polymer TP1 are the same as defined above.

[0155] The conversion of the polymer composition P2 comprising the polymer composition P1 and the thermoplastic polymer TP1 is preferably carried out by extrusion.

[0156] The polymer composition P1 is used in the polymer composition P2 in a ratio of between 1 and 20 phr, preferably between 2 and 15 phr, more preferably between 3 and 12 phr and advantageously between 3 and 10 phr.

[0157] The invention also relates to an article comprising a polymer composition P2 as described above. This article may be a profile, a pipe, a siding, a floor membrane, a sheet or a foamed article.

[0158] The present invention also relates to an article comprising a polymer composition P2 as described above as a coextruded layer or as a layer of a laminated structure or as at least one layer of a multilayer structure.

[0159] [Evaluation method] Glass transition temperature The glass transition temperature (Tg) of a polymer or polymer mixture is measured with an apparatus capable of performing thermomechanical analysis. The RDAII "RHEOMETRICSDYNAMIC ANALYSER" proposed by the Rheometrics Company has been used. Thermomechanical analysis accurately measures the changes in the viscoelasticity of a sample as a function of applied temperature, strain or deformation. The frequency used is 1 Hz. The device continuously records the sample deformation while keeping the strain fixed during a controlled temperature change program.

[0160] The results are obtained by plotting the elastic modulus (G'), loss modulus and tan delta as a function of temperature. Tg is the higher temperature value read in the tan delta curve when the derivative of tan delta equals zero.

[0161] To evaluate the volume average powder particle size, particle size distribution and fines ratio, a Malvern Mastersizer 300 device with a 300 mm lens measuring the range of 0.5-880 μm was used. D(v,0.5) is the particle size at which 50% of the sample has a smaller size and 50% of the sample has a larger size, or in other words, the equivalent volume diameter at 50% cumulative volume. This size is also known as the volume median diameter (abbreviated as D50), which is related to the mass or weight median diameter by the particle density, assuming that the density of the particles is independent of size.

[0162] Molecular weight The weight average molecular weight (Mw) of the polymer was measured by size exclusion chromatography (SEC).

[0163] Melting efficiency The melting efficiency of the polymer composition was estimated by measuring the melting time with a torque rheometer based on ASTM D2538-02 (Reapproved 2010). Shorter melting time means better melting efficiency and is interpreted as a more efficient process.

[0164] Melt Strength Melt strength was evaluated by means of a RHEOTENS GOTTFERT apparatus for comparing different melt strengths of various PVC compositions. Roll speed (mm / s) and burst strength (N) at break were reported to evaluate the melt fracture resistance of the different compositions.

[0165] Impact strength The compositions were evaluated for drop weight impact resistance using the ASTM D5420 standard. Normalized average energy to failure (in *lbs / mil) is reported for comparison.

[0166] The double V-notch impact strength was evaluated using the DIN 53753 method. A notch radius of 0.1 mm was used. The impact test was evaluated at controlled room temperature. The pendulum energy was 1 J. The average impact energy was evaluated using 10 samples with their standard deviation. Information on the type of failure (ductile or brittle) is also given.

[0167] Microscopy Microscopy of the powders was performed using a scanning electron microscope (SEM). By detecting backscattered electrons, inorganic fillers, such as calcium carbonate, in the individual powder particles can be easily detected.

[0168] Atomic force microscopy was performed in tapping mode to obtain cantilever dissipated energy information for samples of varying stiffness (due to different glass transition temperatures of the polymer and the inorganic filler). [Example] Use or prepare the following materials: The (meth)acrylic copolymer (A1) is prepared in this way: First (meth) acrylic copolymer (A1a): 8600 g of water, 5.23 g of Na2CO3 and 38.20 g of sodium lauryl sulfate were charged into the reactor under stirring, and the mixture was stirred until completely dissolved. Three vacuum-nitrogen purgings were performed successively and the reactor was placed under a slight vacuum. The reactor was then heated. At the same time, a mixture containing 4166.4 g of methyl methacrylate and 1041.6 g of n-butyl acrylate was nitrogen degassed for 30 minutes. Next, the mixture was quickly introduced into the reactor using a pump. When the temperature of the reaction mixture reached 55°C, 7.81 g of potassium persulfate dissolved in 98.08 g of water was introduced. The pipeline was flushed with 50 g of water. The reaction mixture was heated to the exothermic peak. Then the polymerization was allowed to complete for 60 minutes after the exothermic peak. The reactor was cooled to 30°C and the latex dispersion was taken out. The solid content was 38.2%.

[0170] Second (meth) acrylic copolymer (A1b): 8140 g of water, 5.23 g of Na2CO3 and 38.20 g of sodium lauryl sulfate were charged into the reactor under stirring, and the mixture was stirred until completely dissolved. Three vacuum-nitrogen purgings were performed successively and the reactor was placed under a slight vacuum. The reactor was then heated. At the same time, a mixture containing 3645.6 g of methyl methacrylate and 1562.4 g of n-butyl acrylate was nitrogen degassed for 30 minutes. Next, the mixture was quickly introduced into the reactor using a pump. When the temperature of the reaction mixture reached 55°C, 7.81 g of potassium persulfate dissolved in 98.08 g of water was introduced. The pipeline was flushed with 50 g of water. The reaction mixture was heated to the exothermic peak. Then the polymerization was allowed to complete for 60 minutes after the exothermic peak. The reactor was cooled to 30°C and the latex dispersion was taken out. The solid content was 39.5%.

[0171] The polymeric impact modifier (IM1) was prepared according to the techniques described in US Patent No. 4,278,576 using standard emulsion polymerization techniques.

[0172] The first polymeric impact modifier (IM1a), a core / shell acrylic polymer impact modifier was prepared using 89.2 parts butyl acrylate, 0.4 parts butanediol diacrylate and 0.4 parts diallyl maleate as the elastomeric core followed by polymerization of 10 parts methyl methacrylate. The solids content was 40% of the aqueous dispersion.

[0173] The second polymeric impact modifier (IM1b), a core / shell acrylic polymer was prepared using 84.2 parts of butyl acrylate, 0.4 parts of butanediol diacrylate and 0.4 parts of diallyl maleate as the elastomeric core followed by polymerization of 15 parts of methyl methacrylate. The solids content was 40%.

[0174] The inorganic mineral filler (F1) was calcium carbonate (CaCO3). A slurry or dispersion of CaCO3 was prepared according to the technique described in Japanese Patent 59057913. That is, a slurry was obtained by mixing 270 parts of water, 0.72 parts of sodium polyacrylate and 729.3 parts of CaCO3 having a diameter of 0.2-0.6 μm and 0.6% moisture and stirring for 20 minutes at a shear rate of 5 x 102 / s. The resulting solid content was 73% by weight.

[0175] As thermoplastic polymer TP1, polyvinyl chloride PVC S110P from Kemone was used.

[0176] As flow aid (F2), calcium carbonate (PCC, 0.07 micron) was used.

[0177] The sample compositions according to Table 1 were prepared in powder form as polymer composition P1 or as a comparative example composition.

[0178] Comparative Example 1: The impact modifier dispersion (IM1a) and the mineral filler slurry (F1) were mixed in the following ratio: 7.902 kg (7902 parts) of latex and 1.587 kg (1587 parts) of slurry and spray dried under the conditions conventionally used for the dispersion itself. The particle size of the resulting powder was ~150 μm. 3 wt% calcium carbonate (PCC, 0.07 micron) was added to the recovered powder as a flow aid (F2). The resulting powder had a ratio of 70 / 30 acrylic impact modifier / inorganic compound CaCO3.

[0179] Comparative Example 2: The impact modifier dispersion (IM1a) and the mineral filler slurry (F1) were mixed in the following ratios: 5.895 kg (5895 parts) of latex and 2.469 kg (2469 parts) of slurry and spray dried under the conditions conventionally used for the dispersion itself. The particle size of the resulting powder was ˜150 μm. 3 wt.% calcium carbonate (PCC, 0.07 μm) was added to the recovered powder as a flow aid (F2). The resulting powder had a ratio of 55 / 45 impact modifier / inorganic compound CaCO 3 .

[0180] Comparative Example 3: For this comparative example, each component was spray dried separately and the resulting powder was then mixed with 3 wt% calcium carbonate (PCC, 0.07 micron) as a flow aid. Sufficient impact modifier dispersion (IM1a) was spray dried to obtain 2122 grams of powder. Sufficient processing aid (meth) acrylic copolymer (A1a) dispersion was spray dried to obtain 235.8 grams of powder. Sufficient calcium carbonate slurry was spray dried to obtain 1800 grams of calcium carbonate. These three amounts of powder were dry blended with 128.6 grams of calcium carbonate (PCC, 0.07 micron) to obtain a dry blended composite.

[0181] Example 1: Two acrylic dispersions and inorganic slurries were mixed in the following ratios: 5.305 kg (5305 parts) of impact modifier dispersion (IM1a), 0.617 kg (617 parts) of processing aid (meth) acrylic copolymer (A1a) and 2.469 kg (2469 parts) of inorganic mineral filler slurry (F1) and spray dried under conditions conventionally used for the dispersion itself. The particle size of the resulting powder was ~150 μm. 3 wt% calcium carbonate (PCC, 0.07 micron) was added to the recovered powder as a flow aid (F2). The resulting powder had a ratio of 55 / 45 polymer / inorganic compound CaCO3.

[0182] Example 2: Example 1 was repeated but using impact modifier dispersion (IM1b) instead of impact modifier dispersion (IM1a).

[0183] Example 3: Example 1 was repeated but using (meth)acrylic copolymer (A1b) instead of (meth)acrylic copolymer (A1a).

[0184] Table 1 Composition of powder samples

[0185] The powdered samples of the comparative examples and examples of Table 1 were formulated at 5.5 phr in a PVC composition with PVC as thermoplastic polymer TP1. The composition was dry blended in a Papenmeyer apparatus at elevated temperature. The PVC compositions were prepared according to the amounts given in Table 2.

[0186] Table 2 - PVC compositions *Composition for GARDNER drop weight impact strength.

[0187] The different compositions of Table 2 were extruded in a Haake Polylab extruder. During extrusion, the average torque and melt pressure were followed.

[0188] The results are summarized in Table 2.

[0189] Table 3 - Evaluation of the Examples and Comparative Examples of Table 1 during the conversion and extrusion of the compositions of Table 2

[0190] Examples 1 to 3 exhibit lower torque and melt pressure while having better or acceptable melt times, especially much higher roll speeds and burst strengths at break, allowing faster extrusion due to better resistance to melt fracture.

[0191] Comparative Examples 1 and 2 have higher melt pressure and torque and lower roll speed and burst strength at break, while Comparative Example 3 has higher melt pressure and torque.

[0192] The test specimens were prepared from extruded samples according to the composition of Table 2, while using the examples and comparative examples of the powder sample compositions of Table 1. Impact properties were measured on the test specimens and the results are listed in Table 4.

[0193] Table 4 - Evaluation of the impact properties of the examples and comparative examples of Table 1 after conversion and extrusion of the compositions of Table 2 nm – not measured.

[0194] Compared to the comparative example, Examples 1 and 2 exhibit the same level or even higher dart impact strength, while the compositions contain less impact modifier.

Claims

1. A polymer composition P1 in powder form, comprising: a) 40 to 50% by weight of an inorganic mineral compound F, b) 4 to 10% by weight of a (meth)acrylic copolymer A1 or a mixture of (meth)acrylic copolymers A1, c) a polymeric impact modifier IM1 or a mixture of polymeric impact modifiers IM1, wherein the polymeric impact modifier IM1 is a polymer particle having a multilayer structure comprising at least one layer IM1L1 comprising a polymer L1 having a glass transition temperature below 0°C and at least one other layer IM1L2 comprising a polymer L2 having a glass transition temperature above 45°C and having a weight average particle size (diameter) between 20 nm and 500 nm, Features The three components a), b) and c) add up to 100% by weight, and The weight ratio of layer IM1L1 / layer IM1L2 in the polymer particles having a multilayer structure is between 87 / 13 and 97 / 3, And the polymer L1 is a (meth)acrylic polymer comprising at least 50% by weight of monomers derived from alkyl acrylate.

2. A composition according to claim 1, wherein the inorganic mineral compound F consists of a mineral filler F1 and a flow aid F2, wherein the weight ratio F1 / F2 is at least 5 / 1.

3. A composition according to claim 1 or 2, comprising a) between 40% and 50% by weight of an inorganic mineral compound F, b) between 4% and 10% by weight of the (meth)acrylic copolymer A1 and c) Polymeric impact modifier IM1.

4. The composition according to claim 1 or 2, wherein the composition is in the form of a powder having a volume median particle size D50 between 1 μm and 500 μm.

5. A composition according to claim 4, wherein each powder particle comprises compounds a), b) and c).

6. The composition according to claim 1 or 2, wherein the polymeric impact modifier IM1 is a polymer particle having a multilayer structure comprising at least one layer IM1L1 comprising a polymer L1 having a glass transition temperature of -100°C to 0°C and at least another layer IM1L2 comprising a polymer L2 having a glass transition temperature of 60°C to 150°C. 7 . The composition according to claim 6 , wherein the weight ratio of layer IM1L1 / layer IM1L2 in the polymer particles having a multilayer structure is within a weight range of 89 / 11 to 96 / 4.

8. The composition according to claim 7, wherein the weight ratio of layer IM1L1 / layer IM1L2 in the polymer particles having a multilayer structure is within a weight range of between 90 / 10 and 96 / 4.

9. The composition according to claim 6, wherein a weight ratio of layer IM1L1 / layer IM1L2 in the polymer particles having a multilayer structure is within a weight range of 88 / 12 to 97 / 3.

10. The composition according to claim 6, wherein the polymer L1 constitutes more than 85% by weight of the polymeric impact modifier IM1.

11. The composition according to claim 6, wherein the polymer L1 constitutes more than 86% by weight of the polymeric impact modifier IM1.

12. A composition according to claim 1 or 2, wherein at least a part of the inorganic mineral compound F is a mineral compound chosen from calcium carbonate, pyrogenic or precipitated silica, clay, zeolite or perlite, titanium dioxide.

13. The composition according to claim 12, wherein the clay is calcined clay or montmorillonite as a nanoclay.

14. A composition according to claim 1 or 2, wherein the inorganic mineral compound F is chosen from calcium carbonate.

15. The composition according to claim 1 or 2, wherein the (meth)acrylic copolymer A1 is selected from copolymers comprising at least 50% by weight of methyl methacrylate.

16. The composition according to claim 1 or 2, wherein the (meth)acrylic copolymer A1 has a weight average molecular weight of at least 1,000,000 g / mol.

17. A method for preparing a polymer composition P1, the polymer composition P1 comprising a) 40% to 50% by weight of an inorganic mineral compound F consisting of a mineral filler F1 and a flow aid F2, wherein the weight ratio F1 / F2 is at least 5 / 1, b) 4 to 10% by weight of a (meth)acrylic copolymer A1, c) a polymeric impact modifier IM1, wherein the polymeric impact modifier IM1 is a polymer particle having a multilayer structure comprising at least one layer IM1L1 comprising a polymer L1 having a glass transition temperature below 0° C. and at least another layer IM1L2 comprising a polymer L2 having a glass transition temperature above 45° C. and having a weight average particle size (diameter) between 20 nm and 500 nm, Features The three components a), b) and c) add up to 100% by weight, and The weight ratio of layer IM1L1 / layer IM1L2 in the polymer particles having a multilayer structure is between 87 / 13 and 97 / 3, and the method comprises the following steps: i) blending the three components a), b) and c), wherein the three components are in the form of a dispersion in the aqueous phase during the blending step, ii) drying the blend obtained in step i).

18. A process for preparing a polymer composition P2 comprising a polymer composition P1 according to any one of claims 1 to 16 or a polymer composition P1 obtained by a process according to claim 17, The polymer composition P2 further comprises d) Thermoplastic polymer TP1 The method comprises the following steps: The composition P1 and the thermoplastic polymer TP1 are blended.

19. Use of a composition according to any one of claims 1 to 16 or a composition obtained by a process according to claim 17 for increasing the melt fracture resistance of a thermoplastic polymer TP1.

20. Use of a composition according to any one of claims 1 to 16 or a composition obtained by a process according to claim 17 for transforming a polymer composition P2 comprising said polymer composition P1 and a thermoplastic polymer TP1.

21. An article comprising a polymer composition converted according to claim 20, characterized in that The product is a profile, a pipe, a siding, a floor membrane, a sheet or a foamed product.

Citation Information

Patent Citations

  • Production of high concentration slurry of synthetic calcium carbonate having good fluidity

    JP1984057913A

  • Acrylic copolymer for use in highly filled composites

    US20090111915A1

  • Vinyl polymer compositions

    US3373229A

  • Isolation and improvement of impact modifier polymer powders

    US4278576A

  • Composite polymer modifiers

    WO2010099160A1